THE SIGNIFICANCE OF BLACK IRONY IN POSTMODERN PROSE - Mukhlisa Vakhobovna Tursunova (International Scientific and Current Research Conferences, 2021)
The article is inclined to investigate black irony as one of the major characteristics of postmodern literary trend of the second half of the XX century. The studies carried out on black irony can both theoretically and practically enhance postmodern readers’ credit of the authors’ motives in context.